The role of Food Science and Foodomics in the implementation of One-Health - Ibáñez, Elena; Zhang, Zhaowei; Cifuentes, Alejandro (Frontiers in Nutrition, 2025)
The concept of One-Health recognizes that the health of people is closely connected to the health of animals and our shared environment. Despite the most frequent applications of One-Health approaches have been in the control of parasitic and infectious (zoonotic) diseases shared between humans and animals, many other areas of implementation should be explored that will help to overcome some of the current planetary challenges. In this work, we discuss for the first time the multiple possibilities of advancing the development of One-Health through future applications of Food Science and Foodomics, showing a vast and unexplored area of research. We also discuss the emerging potential of synthetic biology for Food Science and how it can help to achieve the One-Health goals.